A multifunctional surface care material and its preparation method and application
By applying multifunctional surface maintenance materials of silicone and metal complexes, hydrophilic layers and hydrophobic layers on military weapons, rust and corrosion problems are solved, and the protection and performance improvement of metal surfaces are achieved.
Patent Information
- Application Number
- CN202310885489.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-07-18
AI Technical Summary
Existing composite materials cannot effectively prevent rust and corrosion problems in military weapons, especially in humid or extremely cold environments, resulting in increased metal brittleness and decreased performance.
Using multifunctional surface maintenance materials, including complexes formed by silicone and free iron in metal products, water-absorbing layers containing hydrophilic groups or gel structures, and hydrophobic layers of aliphatic compounds, through organic complexing layers In close bonding with metal, the hydrophilic layer adsorbs moisture, and the hydrophobic layer prevents water vapor from invading, forming a crosslinked structure to protect the metal surface.
Effectively prevent free iron from rusting, repairing metal surface defects, reducing the impact of moisture on metal, maintaining the hydrophobic state of metal surface, extending the service life of the weapon and improving performance under low temperature conditions.
Smart Images

Figure CN117343639B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite materials, and in particular to a multifunctional surface care material and a preparation method and application thereof. Background Art
[0002] With the rapid development of polymer materials, composite materials are increasingly used in production or life. Due to their wide sources, high strength, light weight, excellent mechanical and heat-resistant, wear-resistant properties, they have penetrated into various fields of national development.
[0003] As weapons and equipment develop towards lightweight, composite materials naturally come into people's view. This is because most military weapons are made of steel products, which are prone to rust. Especially after rain, the trigger part will rust, causing the gun to fail completely. Even if gun oil is used normally, rust is still unavoidable. In low temperature areas or even extremely cold areas, the viscosity of gun oil increases and even solidifies, causing large areas of weapons to be scrapped.
[0004] When it snows, the rapidly dropping temperature not only increases the brittleness of steel products, changes the crystal structure inside the metal, and makes them prone to rust; when weapons are exposed to humid air, they will re-condense inside the weapon when shot, further exacerbating the severity of rust; in addition, the corrosiveness of the combustion gases will cause the surface of the components to be rough, and once frozen, they will adhere strongly and not fall off easily, which can easily cause accidents.
[0005] At present, composite materials used in weapons are mainly used in handguards, stocks and magazines, and the above-mentioned rust problems of firearms are still not solved; there are also composite materials for military firearm packaging, but they cannot avoid the corrosion of metal by moisture in the air when the firearm is in use; and gun barrels are produced using the carbon fiber tube-in-tube process, but there is an air gap between the stainless steel gun barrel and the carbon fiber tube, and the above-mentioned problems will still occur in humid or cold areas, and the carbon fiber will become brittle and have poor impact resistance in extremely cold weather. Summary of the invention
[0006] In view of the above-mentioned problems, the present application proposes a multifunctional surface maintenance material; an organic complexing layer, a hydrophilic layer and a hydrophobic layer are arranged on the surface of a metal product, and the organic complexing layer is complexed with the metal product so as to be tightly combined with the surface of the metal product and repair the defects on the metal surface; the hydrophilic layer can store a certain amount of water to reduce the influence of water on the metal, and the hydrophobic layer can prevent the intrusion of water vapor; and when the temperature of the metal product is high, the water in the hydrophilic layer can absorb heat and evaporate, thereby playing a role in lowering the temperature, thereby overcoming the deficiencies and defects mentioned in the background technology.
[0007] To achieve the above objectives, this application adopts the following technical solutions:
[0008] The invention of this application is to provide a multifunctional surface care material, including: an organic complex layer connected to the metal product, a hydrophilic layer connected to the organic complex layer, and a hydrophobic layer covering the gel structure; the organic complex layer is a complex formed by organic silicon and free iron in the metal product; the water-absorbing layer is a mesh or gel structure containing a hydrophilic group; the hydrophobic layer is an aliphatic compound.
[0009] Optionally, the organosilicon includes polysiloxane substituted with alkyl, alkenyl or alkynyl groups; the network or gel structure containing hydrophilic groups includes polymers of enol, alkenyl acid or alkenyl amide containing or not containing substituents; the aliphatic compound is a polymer formed by alkyl, alkenyl, alkynyl and / or alkenyl, alkynyl groups containing substituents.
[0010] Optionally, the organic complexing layer also reacts with the hydrophobic layer in situ to form a cross-linked structure.
[0011] Optionally, the thickness of the organic complex layer is 7-15 μm; the thickness of the hydrophilic layer is 1-5 μm; and the thickness of the hydrophobic layer is 5-10 μm.
[0012] Another inventive point of the present application is to provide a method for preparing any of the above multifunctional surface care materials, comprising: (1) adding a precursor monomer of silicone to solvent I to obtain solution I; (2) adding a precursor of a network or gel structure containing a hydrophilic group to solvent II to obtain solution II; (3) adding a precursor of an aliphatic compound to solvent III to obtain solution III; (4) applying solution I, solution II and solution III to the surface of a metal product in sequence, and curing them to obtain the multifunctional surface care material.
[0013] Optionally, the curing conditions are: temperature of 50-80° C. and time of 20-60 min.
[0014] Optionally, in step (1), the solvent I is water, and the precursor monomer of the organosilicon undergoes a hydrolysis reaction with water.
[0015] Optionally, the precursor monomer of the organosilicon includes chlorine-containing silane.
[0016] Optionally, the molar ratio of solvent I to the precursor monomer of organic silicon is not less than 3:1.
[0017] Another inventive point of the present application is to provide an application of any of the above-mentioned multifunctional surface care materials on the surface of metal products.
[0018] Compared with the prior art, this application has the following beneficial effects:
[0019] (1) The present application sets an organic complexing layer on the metal surface that can complex with the metal, and complexes with the free iron in the metal, thereby preventing the free iron from rusting; at the same time, it can fill the defective areas to avoid subsequent impurity deposition and other problems. The hydrophilic layer cross-linked with the organic complexing layer has a hydrophilic mesh structure or gel structure, which can absorb the moisture around the metal, thereby avoiding the influence of moisture on the metal; the hydrophobic layer is located on the outside of the hydrophilic layer to avoid excessive infiltration of moisture, thereby maintaining the hydrophobic state of the metal surface.
[0020] (2) The present application obtains the multifunctional surface care material by in-situ polymerization. During the in-situ polymerization, when the organic complex layer and the hydrophilic layer are generated at the same time, cross-linking can also occur, thereby ensuring the chemical bonding between the two layers. The hydrophobic layer aliphatic compound can be an alkane, an alkene or an alkyne. When the organic complex layer and the hydrophilic layer are generated at the same time, a substitution reaction is carried out to form a hydrophobic layer with a long hydrocarbon chain on the outer layer of the hydrophilic layer. The hydrophobic layer can also be a polymer formed by alkenyl or alkynyl. When the organic complex layer and the hydrophilic layer are generated at the same time, a cross-linking reaction is carried out to cross-link with the organic complex layer and the hydrophilic layer at the same time to cover the hydrophilic layer. At the same time, when the hydrophilic layer is generated, a large amount of heat is generated, and the organic complex layer is heated to remove moisture and increase the molecular weight of the organic complex layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic diagram of the structure of a multifunctional surface care material provided in one embodiment of the present application;
[0022] Figure 2 A schematic structural diagram of a multifunctional surface care material provided in one embodiment of the present application.
[0023] The reference numerals in the accompanying drawings are as follows:
[0024] 1 Metal
[0025] 2 Organic complex layer
[0026] 3 Hydrophilic layer
[0027] 4 Hydrophobic layer DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below. However, it should be understood that the description here is only used to explain the present application and is not used to limit the scope of the present application.
[0029] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present application, and the terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The reagents and instruments used herein are all commercially available, and the characterization means involved can refer to the relevant descriptions in the prior art, which will not be repeated herein.
[0030] In order to further understand the present application, the present application is further described in detail below in conjunction with the best embodiment.
[0031] Example 1
[0032] This embodiment provides a multifunctional surface care material, including: an organic complex layer connected to the metal product, a hydrophilic layer connected to the organic complex layer, and a hydrophobic layer coating the gel structure; the organic complex layer is a complex formed by organic silicon and free iron in the metal product; the water-absorbing layer is a mesh or gel structure containing a hydrophilic group; and the hydrophobic layer is an aliphatic compound.
[0033] like Figure 1 As shown, the organic complex layer is in direct contact with the surface of the metal product, the hydrophilic layer is located outside the organic complex layer, and the outermost layer is the hydrophobic layer. The hydrophobic layer can make the metal surface hydrophobic and reduce the possibility of rust; the hydrophilic layer will absorb the water entering the metal surface, prevent the water from further diffusing to the metal, and block the contact between the water and the metal; the organic complex layer complexes with the free iron of the metal to further reduce the possibility of rust; at the same time, it repairs the defects on the metal surface to avoid more exposure of metal elements.
[0034] Silicones include polysiloxanes substituted with alkyl, alkenyl or alkynyl groups; they may be polysiloxanes containing only saturated groups or unsaturated polysiloxanes, for example, containing alkenyl, alkynyl, etc.; unsaturated polysiloxanes may also undergo addition reactions with hydrophilic layers or water-absorbing layers during polymerization to form more complex structures.
[0035] Polysiloxane is an organic polymer with a silicon-oxygen-silicon structure. It can maintain its physical properties over a wide temperature range, which makes it suitable for weapons and equipment that need to be used in severe cold conditions. It also has outstanding low-temperature flexibility.
[0036] The network or gel structure containing hydrophilic groups includes polymers of enols, enolic acids or enamides with or without substituents; the resulting polymers have good water solubility and high chemical activity due to the presence of hydroxyl groups, carboxyl groups or amide groups and the ease of forming hydrogen bonds; and can be grafted and cross-linked with the organic complex layer during polymerization, thereby being able to form a tight connection with the organic complex layer.
[0037] The aliphatic compound is an alkyl group, an alkenyl group, an alkynyl group and / or a polymer formed by an alkenyl group and an alkynyl group containing a substituent.
[0038] Alkyl, alkenyl and alkynyl groups containing substituents, wherein the substituents may be halogens, such as F, Cl, Br, and I; the carbon number of the alkyl, alkenyl and alkynyl groups is C5 to C20; preferably, the alkyl, alkenyl and alkynyl groups may be chain alkyl, cycloalkyl, cycloalkenyl, bicycloalkyl, chain alkenyl, aryl, naphthyl, biphenyl and chain alkynyl groups.
[0039] The polymers formed by alkenyl and alkynyl groups containing substituents include high molecular organic substances formed by the polymerization of chain alkenyl, cyclic alkenyl or chain alkynyl groups, and the polymers may be, for example, polyethylene, polypropylene, polydibutylene, etc.; the polymers containing substituents may be, for example, vinyl chloride, allyl chloride, etc.
[0040] The organic complexing layer also reacts in situ with the hydrophobic layer to form a cross-linked structure; e.g. Figure 2 As shown, the cross-linked structure formed by the organic complex layer and the hydrophobic layer makes the structure of the metal surface a large whole through mutual cross-linking between the layers, which is firmly attached to the surface of the metal and plays a role in repairing and protecting the metal.
[0041] When the organic complex layer is an unsaturated polysiloxane, for example, containing alkenyl, alkynyl, etc., it can undergo addition reaction with the polymer formed by the alkenyl and alkynyl groups of the hydrophobic layer to form a large network structure; it can also undergo substitution reaction with the alkyl, alkenyl, and alkynyl groups containing substituents in the hydrophobic layer to form a large network structure; thereby, the hydrophilic layer is coated in the middle of the hydrophobic structure to further reduce the infiltration of water.
[0042] The thickness of the organic complex layer is 7 to 15 μm; it can be 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm. If the thickness of the organic complex layer is too thin, the hydrophilic layer is too close to the metal surface, and the water in the hydrophilic layer is more likely to contact the metal, causing the metal to corrode faster; if the thickness is too thick, it is not conducive to heat conduction, causing local overheating, and is not conducive to the heat dissipation of the metal surface.
[0043] The hydrophilic layer is 1~5μm; it can be 1μm, 2μm, 3μm, 4μm or 5μm. When the hydrophilic layer is too thick, the hierarchical structure of the metal surface will be too soft and the viscosity will increase; in addition, it will cause too much water to be stored, increase the load on the metal surface, and be unfavorable for the drying of the metal surface; when the hydrophilic layer is too thin, it cannot play a good role in absorbing water, so that water can easily contact the metal.
[0044] The hydrophobic layer is 5~10μm. The hydrophobic layer needs to have a certain thickness to block water vapor, but if it is too thick, the heat transfer efficiency will be too slow.
[0045] Example 2
[0046] This embodiment provides a method for preparing a multifunctional surface care material. The multifunctional surface care material is the same as the multifunctional surface care material described in Example 1, and will not be described in detail here.
[0047] The method comprises: (1) adding a precursor monomer of organic silicon into a solvent I to obtain a solution I; (2) adding a precursor having a network or gel structure containing a hydrophilic group into a solvent II to obtain a solution II; (3) adding a precursor of an aliphatic compound into a solvent III to obtain a solution III; (4) applying the solution I, solution II and solution III sequentially onto the surface of a metal product, and curing the solution to obtain the multifunctional surface care material.
[0048] The precursor monomer of the organosilicon includes a halogen-substituted silane, and the halogen is preferably chlorine, that is, the precursor monomer of the organosilicon preferably includes a chlorine-containing silane; the precursor monomer can be a halogen-substituted silane of a saturated group, for example, it can be dimethyldichlorosilane, methyltrichlorosilane, diethyldichlorosilane, methylethyldichlorosilane, dipropyldichlorosilane, ethylpropyldichlorosilane, methylpropyldichlorosilane, dibutyldichlorosilane, ethyltrichlorosilane, propyltrichlorosilane, butyltrichlorosilane, etc.; the precursor monomer can be an unsaturated halogen-substituted silane, for example, it can be methyl-acryl-dichlorosilane, methyltrichlorosilane, etc.
[0049] The solvent I is preferably water. The precursor monomer of the organosilicon can undergo a hydrolysis reaction in water.
[0050] In step (1), the precursor monomer of the organosilicon undergoes a hydrolysis reaction to generate an intermediate containing a hydroxyl group.
[0051] The molar ratio of solvent I to the precursor monomer of the organosilicon is not less than 3:1, preferably (3-10):1, and can be 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1. At this ratio, the precursor monomer of the organosilicon undergoes hydrolysis reaction to the greatest extent without undergoing dehydration or dehydrochlorination reaction, that is, in this step, the amount of polysiloxane generated is relatively small; the purpose is to carry out in-situ polymerization later, so the polymerization reaction in the early stage should be minimized.
[0052] The precursor of the network or gel structure containing a hydrophilic group includes substituted or unsubstituted enols, olefinic acids or olefinic amides; for example, substituted or unsubstituted acryl alcohol, acrylic acid, acrylamide.
[0053] Solution II also includes an initiator, which includes an inorganic initiator and / or an organic initiator.
[0054] Inorganic initiators include potassium persulfate, ammonium persulfate, sodium perbromide or hydrogen peroxide.
[0055] Organic initiators include benzoyl peroxide, lauroyl peroxide, tert-butyl hydroxy peroxide, azobisisobutyronitrile, azobisdimethylvaleronitrile, sodium azobiscyanovalerate, and the like.
[0056] Solvent II is water. After the precursor of the network or gel structure containing a hydrophilic group is mixed with water, an initiator is added before coating to prevent premature polymerization.
[0057] Preferably, the mass ratio of the initiator to the precursor of the network or gel structure containing a hydrophilic group is 1:(10-30).
[0058] The precursor of the network or gel structure containing hydrophilic groups is dissolved in water, then an initiator is added and quickly coated on the metal surface.
[0059] The precursor of the aliphatic compound is an alkyl group, an alkenyl group, an alkynyl group containing a substituent and / or a polymer formed by an alkenyl group or an alkynyl group containing a substituent.
[0060] When the precursor of the aliphatic compound is an alkyl, alkenyl or alkynyl group which may or may not contain a substituent, it is preferably a halogen-substituted alkyl, alkenyl or alkynyl group, which may be a C5 to C20 halogenated alkyl, alkenyl or alkynyl group; for example, perfluorobutylethylene and cyclopentene.
[0061] When the aliphatic compound is a polymer, the aliphatic compound precursor is a polyolefin or polyalkyne containing a substituent, which may be polyvinyl chloride, polypropylene chloride, polydichloroprene, polychloroprene, polypentene chloride, or the like.
[0062] Through grafting and cross-linking with the organic complex layer and the hydrophilic layer, the heat resistance, wear resistance and corrosion resistance of the aliphatic compound can be greatly improved, thus better meeting the needs of metal products.
[0063] The precursor of the aliphatic compound is dissolved in an organic solvent, a catalyst is added, and then coated on the metal surface.
[0064] The catalyst includes organic catalyst and / or inorganic catalyst; the organic catalyst includes tin salt, metal halogen salt, sulfate, etc.; the inorganic catalyst includes potassium hydroxide, sodium carbonate or sodium bicarbonate, etc.
[0065] The solvent III is water; the solution III also includes a dispersant and an initiator; the dispersant includes one of gelatin, polyvinyl alcohol, carboxymethyl cellulose or hydroxypropyl cellulose; the initiator includes one or more mixtures of diisopropyl peroxydicarbonate, azobisisoheptonitrile, dodecyl peroxide, acetyl cyclohexane sulfonic acid or dicyclohexyl peroxydicarbonate.
[0066] When solution I is applied to the metal surface, it is partially dried so that the layer generates a low polymer of polysiloxane that can partially adhere to the metal surface; then solution II is applied on top of the first layer and also partially dried so that the organic complex layer and the hydrophilic layer are partially cross-linked; finally, solution III is applied.
[0067] After all coating is completed, heating and curing are performed to finally obtain a multifunctional surface care material.
[0068] The curing conditions are: temperature 50~80℃, time 20~60min.
[0069] During the heating process, the exothermic polymerization reaction of the hydrophilic layer will further dehydrate or dehydrochlorinate the organic complex layer, resulting in the generation of a large amount of polysiloxane and increasing the molecular weight of polysiloxane; at the same time, polysiloxane cross-links with the hydroxyl, carboxyl or amide groups of the hydrophilic layer to enhance the connection between the two layers. The moisture released by the organic complex layer causes the hydrophilic layer to contain some moisture, causing its degree of polymerization to slightly decrease, forming a gel or mesh structure with a certain elasticity. Due to the heat release of the hydrophilic layer, the temperature of the hydrophobic layer also rises greatly, thereby undergoing condensation or cross-linking reactions with the hydrophilic layer, and finally forming a multifunctional surface care material with a three-layer structure.
[0070] Example 3
[0071] According to the content of this application, the multifunctional surface care material of Example 1 and the preparation method of Example 2 are specifically described, and the specific description is as follows:
[0072] Test Example 1
[0073] (1) Add 150 parts of dimethyldichlorosilane to 450 parts of water and mix well to obtain solution I. Apply solution I to the surface of 416 stainless steel and air-dry for 5 minutes.
[0074] (2) Dissolve 20 parts of acrylamide in 180 parts of water, mix well, add 1 part of ammonium persulfate, and quickly apply it on the surface of step (1), and air-dry for 5 minutes.
[0075] (3) Weigh 100 parts of vinyl chloride, 0.8 parts of polyvinyl alcohol, 120 parts of deionized water, 0.1 parts of diisopropyl peroxydicarbonate, and 0.1 parts of potassium hydroxide, mix them evenly to obtain solution III; then apply it on the surface of step (2).
[0076] (4) Then, the metal obtained in step (3) is heated in a nitrogen atmosphere at a temperature of 60° C. for 60 min until the temperature of the metal surface drops to room temperature, thereby obtaining a multifunctional surface care material.
[0077] Test Example 2
[0078] (1) Add 150 parts of vinyl trichlorosilane to 450 parts of water and mix well to obtain solution I. Apply solution I to the surface of 416 stainless steel and air-dry for 5 minutes.
[0079] (2) Dissolve 20 parts of acrylic acid in 180 parts of water, mix well, add 1 part of ammonium persulfate, and quickly apply it on the surface of step (1), and air-dry for 5 minutes.
[0080] (3) Weigh 100 parts of polyvinyl chloride, 0.8 parts of polyvinyl alcohol, 120 parts of deionized water, 0.1 parts of ammonium persulfate, and 1 part of triazole dithioamine salt, mix them evenly to obtain solution III; then apply it on the surface of step (2).
[0081] (4) Then, the metal obtained in step (3) is heated in a nitrogen atmosphere at a temperature of 60° C. for 60 min until the temperature of the metal surface drops to room temperature, thereby obtaining a multifunctional surface care material.
[0082] Test Example 3
[0083] (1) Add 150 parts of methyl-acryl-dichlorosilane to 450 parts of water and mix well to obtain solution I. Apply solution I to the surface of 416 stainless steel and air-dry for 5 minutes.
[0084] (2) Dissolve 20 parts of acrylamide in 180 parts of water, mix well, add 1 part of ammonium persulfate, and quickly apply it on the surface of step (1), and air-dry for 5 minutes.
[0085] (3) Weigh 100 parts of cyclopentene, 120 parts of toluene and 1 part of aluminum chloride and mix them evenly to obtain solution III; then quickly apply the solution to the surface of step (2).
[0086] (4) Then, the metal obtained in step (3) is heated in a nitrogen atmosphere at a temperature of 60° C. for 60 min until the temperature of the metal surface drops to room temperature, thereby obtaining a multifunctional surface care material.
[0087] Test Example 4
[0088] (1) Add 150 parts of methyl-acryl-dichlorosilane to 450 parts of water and mix well to obtain solution I. Apply solution I to the surface of 416 stainless steel and air-dry for 5 minutes.
[0089] (2) Dissolve 20 parts of acrylamide in 180 parts of water, mix well, add 1 part of ammonium persulfate, and quickly apply it on the surface of step (1), and air-dry for 5 minutes.
[0090] (3) Weigh 100 parts of 6-bromo-1-hexene, 120 parts of methanol, and 1 part of chloroplatinic acid, mix them evenly to obtain solution III; then quickly apply it to the surface of step (2).
[0091] (4) Then, the metal obtained in step (3) is heated in a nitrogen atmosphere at a temperature of 60° C. for 60 min until the temperature of the metal surface drops to room temperature, thereby obtaining a multifunctional surface care material.
[0092] Comparative Example 1
[0093] The process is substantially the same as that of Experimental Example 1, except that step (3) is missing, i.e., there is no hydrophobic layer. The rest is the same as that of Experimental Example 1.
[0094] Comparative Example 2
[0095] The process is substantially the same as that of Experimental Example 1, except that step (1) is missing, i.e., there is no organic complexing layer. The rest is the same as that of Experimental Example 1.
[0096] Comparative Example 3
[0097] The method is substantially the same as that in Experimental Example 1, except that step (2) and step (3) are missing, i.e., there is no hydrophilic layer and hydrophobic layer. The rest is the same as that in Experimental Example 1.
[0098] Comparative Example 4
[0099] 416 stainless steel surface without any treatment
[0100] (1) The state of iron in the metal surface was tested. When free iron exists, it is easy to react with water. The test method is the blue dot test, which is as follows: 5 grams of potassium ferrocyanide K3[Fe[CN]6], 1 milliliter of 98% sulfuric acid and 5 milliliters of 36% hydrochloric acid are added to an appropriate amount of distilled water to prepare a solution with a total volume of 100 milliliters (prepared immediately before use); the solution is directly applied or dripped on the metal surfaces of the test examples and the comparative examples, and the appearance of blue dots is observed, that is, whether blue dots appear and when they appear.
[0101] The basic principle of the blue dot test is that if the surface is contaminated with ferrous ions, there will be ferrous ions, and the following reaction can occur;
[0102] 3Fe2 + + 2[Fe[CN6]] - =Fe3[Fe[CN]6]2 dark blue precipitate can be used to test whether passivation treatment has been performed and to test the passivation effect.
[0103] The time for blue spots to appear in Comparative Examples 2 and 4 is 15 minutes, indicating that there is a certain amount of free iron; no blue spots appear in Test Examples 1 to 4, Comparative Examples 1 and 3 after 24 hours, indicating that the amount of free iron is almost non-existent, that is, the organic complex layer of the present application can combine with the free iron and has good anti-corrosion performance.
[0104] (2) Neutral salt spray tests were carried out on the test examples and comparative examples respectively. The results are shown in Table 1:
[0105] Salt spray resistance test Salt spray resistance test Test Example 1 >4000h Comparative Example 1 <600h Test Example 2 >4000h Comparative Example 2 <100h Test Example 3 >4000h Comparative Example 3 <1000h Test Example 4 >4000h Comparative Example 4 <100h
[0106] As shown in Table 1, in Comparative Example 1, there is no hydrophobic layer, and the hydrophilic layer cannot be protected, so that too much water accumulates in the hydrophilic layer, which makes it easier to contact with the metal, making rust faster. Comparative Example 2 cannot complex the free iron because it does not have an organic complexing layer; at the same time, the hydrophilic layer is in direct contact with the metal. Although a certain amount of water can be absorbed from the inside of the metal, due to the characteristics of the hydrophilic layer, the water is in contact with the metal for a longer time, and the degree of rust is more serious. Comparative Example 3 only contains an organic complexing layer. Although it can delay the time of rusting to a certain extent, due to the limited effect of siloxane, it cannot protect the metal surface for a long time. Comparative Example 4 has no protection and rusts first. However, Test Examples 1 to 4 of the present application have a complete organic complex layer, a hydrophilic layer and a hydrophobic layer, and the layers are cross-linked and bonded to each other to form a stable network structure. The hydrophobic layer can reject most moisture intrusion, and the hydrophilic layer can firmly lock the moisture inside the metal and the moisture that penetrates in to prevent it from extending to the metal layer; the organic complex layer complexes with the free iron in the metal to further prevent the free iron from oxidizing and rusting.
[0107] (3) After being frozen at low temperature (-30℃) for 24 hours, a neutral salt spray test was performed. The results are shown in Table 2:
[0108] Salt spray resistance test Salt spray resistance test Test Example 1 >3800h Comparative Example 1 <200h Test Example 2 >3800h Comparative Example 2 <50h Test Example 3 >3800h Comparative Example 3 <600h Test Example 4 >3800h Comparative Example 4 <50h
[0109] As shown in Table 2, Test Examples 1 to 4 of the present application are almost the same as before freezing, which is far superior to the prior art. The layers are cross-linked with each other, which greatly improves the low-temperature resistance of each layer and can maintain good performance after low temperature.
[0110] In Comparative Example 1, the hydrophilic layer is directly exposed to the air, which results in a high moisture content. After low-temperature freezing, the gel structure solidifies and loses its ability to store water, which then flows to the metal surface. In Comparative Example 2, the free iron is not complexed, and the hydrophilic layer solidifies, losing its ability to store water. In addition, the excessive moisture on the metal surface accelerates the rusting process. Comparative Example 3 contains an organic complexing layer, but since it only has one layer of structure, the degree of grafting and cross-linking is poor in low-temperature resistance, and the anti-rusting ability is slightly reduced. Comparative Example 4, after freezing, changes in the internal lattice of the metal make the rusting more serious.
[0111] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A multifunctional surface care material, characterized in that: include: An organic complexing layer connected to the metal product, a hydrophilic layer connected to the organic complexing layer, and a hydrophobic layer covering the hydrophilic layer; The organic complex layer is a complex formed by organic silicon and free iron in the metal product; the organic silicon includes polysiloxane substituted with alkenyl or alkynyl; The hydrophilic layer is a network or gel structure containing a hydrophilic group; the network or gel structure containing a hydrophilic group includes a polymer of an enol, an ene acid or an ene amide containing a substituent or not containing a substituent; The hydrophobic layer is an aliphatic compound; the aliphatic compound is an alkyl, alkenyl, alkynyl and / or a polymer formed by alkenyl and alkynyl groups containing substituents; The organic complex layer also reacts in situ with the hydrophobic layer to form a cross-linked structure; The thickness of the organic complex layer is 7-15 μm; the thickness of the hydrophilic layer is 1-5 μm; and the thickness of the hydrophobic layer is 5-10 μm.
2. A method for preparing the multifunctional surface care material according to claim 1, characterized in that: include: (1) adding a precursor monomer of organosilicon to a solvent I to obtain a solution I; (2) adding a precursor of a network or gel structure containing a hydrophilic group into solvent II to obtain solution II; (3) adding a precursor of an aliphatic compound into solvent III to obtain solution III; (4) coating solution I, solution II and solution III on the surface of a metal product in sequence, and curing them to obtain the multifunctional surface care material.
3. The preparation method according to claim 2, characterized in that: The curing conditions are: temperature 50~80℃, time 20~60min.
4. The preparation method according to claim 2, characterized in that: In step (1), the solvent I is water, and the precursor monomer of the organosilicon undergoes a hydrolysis reaction with water.
5. The preparation method according to claim 2, characterized in that: The precursor monomer of the organic silicon includes chlorine-containing silane.
6. The preparation method according to claim 2, characterized in that: The molar ratio of solvent I to the precursor monomer of organic silicon is not less than 3:
1.
7. Use of the multifunctional surface care material according to claim 1 on the surface of metal products.
Citation Information
Patent Citations
Self-repairing composite coating, application of self-repairing composite coating, anticorrosion material and preparation method of anticorrosion material
CN110142190A